Improvement of drill system for the third deep ice coring project around Dome Fuji, Antarctica - Focusing on selection of drilling fluids - - Furusaki, Atsushi; Motoyama, Hideaki; Takata, Morimasa; Nakazawa, Fumio; Kawamura, Kenji; Matoba, Sumito; Mori, Shoichi; Sato, Yosuke; Shinbori, Kunio; Miyahara, Morihiro; Kobayashi, Akio; Yoshise, Yasushi; et al. (2019)
The Tenth Symposium on Polar Science/Ordinary sessions: [OM] Polar Meteorology and Glaciology, Wed. 4 Dec. / Entrance Hall (1st floor) , National Institute of Polar Research conference object